Microbiota das mãos de enfermeiras, estudantes universitários e técnicos de laboratório associada à lavagem higiênica - Rocha, Lílian Alves (2007)
Handwashing frequency may result in harmful effects on the skin, promoting the increase of the prevalence of nosocomial important microorganisms. This study purpose was to assess the quantitative and qualitative changes of the total microbiota (both permanent and transient) from hands of nursing professionals and university laboratory technicians and students due to the irritant action provoked by frequent washing and/or wearing gloves. Sixty health professionals were enrolled from whom collections were performed by the sterile polyethylene bag, before and after washing hands with 3 mL of nonantimicrobial soap for 30 seconds. In the group formed by students and laboratory technicians (n=30), these collections were performed before and after consecutive washings with water and soap. Damaged hands health professionals hands contamination was higher when compared with healthy hands. Hygiene proved to be efficient in both students and laboratory technicians without complaints of irritation after successive washings, a fact not seen among health care workers. Nurses with damaged hands presented higher frequency of S. aureus, Gram negative bacteria and yeast than the healthy ones (P>0.05), as well as the sum of these microorganisms (P=0.07) and presence of S. haemolyticus (P=0.02). The frequency of S. aureus and antimicrobial resistant Gram negative bacteria was higher among nurses damaged hands. The irritation caused on the skin by the frequent washing and/or wearing of gloves may cause changes of hands microbiota and should be considered when choosing hygiene products.